Effectiveness of Incentive Spirometry in Preventing Postoperative Pulmonary Complications after Laparotomy (Medical Forum Monthly, 2024)
Objective: To compare the effectiveness of incentive spirometry with deep breathing exercises in preventing post operative pulmonary complications after laparotomy.Study Design: Observational Analytic study Place and Duration of Study: This study was conducted in the Department of General Surgery, CMH Abbotabad from Jan 2014 to Mar 2015.Materials and Methods: Total of 100 patients fulfilled the inclusion criteria. Patients of both sex and different age groups were included in the study.50 patients underwent deep breathing exercises and 50 patients underwent incentive spirometry postoperatively in addition to deep breathing exercises for five days. ABGs and the temperature was monitored for five days postoperatively. The findings were recorded and analyzed on SPSS 20.Results: The mean age for deep breathing exercises was 40 + 13.34 and for IS was 43+12.76..the male :female ratio was 1.34:1 for deep breathing exercises and 1.8:1 for incentive spirometry. In group A 52% had no post pulmonary complications while incidence of PPC varied with grade 01 (30%) ,grade 2 (10%) and grade 3(6%) .In group B 74% had no post operative pulmonary complication while incidence of PPC varied with grade 01(18%) ,grade 02(6%) and grade 3(2%).Conclusion: Our study showed that the use of incentive spirometry along with deep breathing exercises decreases the incidence of postoperative pulmonary complications as compared to deep breathing exercises alone.